Optimizing Supply Chain Management Strategies for Sustainable Economic Growth in Business - Gabrielle, Gibrania (Maroon Journal De Management, 2024)
In this research, the effect of supply chain optimization strategy on the business performance was tested and the aspect of sustainable economic growth among the businesses in the city of Bandung, Indonesia was examined. They adopted a survey layout; quantitative and the respondent group constituted 150 companies distributed to the manufacturing, services and technology sectors. These four most important supply chain practices which include; demand forecasting, inventory management, supplier relation, and logistics efficiency were put into consideration relative to performance measures which contained revenue growth, profitability, returns on the investment, and share in the market. The results of the correlation, regression, ANOVA and ANCOVA proved that the effective forecasting of the demand, its management, an effective pricing and inventory acted as the key determinants of the financial performance, whereas the successful supplier relations and successful logistics became the important factors influencing the competitiveness of the market. Moreover, the experiment revealed that integrated supply chains techniques were better than pitting ones in generating superior business performance. All in all, results of this kind once again demonstrate the relevance of end-to-end supply chain strategies when it comes to making their operations more effective, resilient, and capable of sustainable growth. The skills generated in this study provide hands-on recommendations to corporate administrators that attempt to enhance the efficiency of the supply chain and policy-makers, who ought to strengthen regional supply chains through embracing technologies, and develop strategic alliances.